ENHANCING STUDENTS' ORAL COMMUNICATION IN DESCRIBING ROOM USING PjBL METHOD - Lailiyah; Nur Hilda (PROCEEDING UMSURABAYA, 2024)
This research examines improving students' oral communication in describing rooms using the PjBL method. This research uses quantitative research with an experimental research design with pretest-posttest and treatment and uses snowball sampling techniques in the experimental class (X-5) and control class. The subjects of this research were students in classes X-3 and X-5 at SMA Muhammadiyah 10 Surabaya. Data collection uses pretest-posttest to determine students' understanding of the experimental class. Treatment will be given to determine students' understanding. Data analysis techniques use normality tests, homogeneity tests, and t-tests. Based on data analysis, there is a significant relationship between oral communication students' and the PjBL method, the pretest significance value in the normality test is .014 > .005 and .010 and the post-test is .019 >.005 and .012 > .005, the significance value of the homogeneity test in the pretest, 383 >.005 and posttest .341 >.005 then next t-test to test the hypothesis the pretest significance value is .002<.005 and posttest is .001<.005 after the t-test the researcher tested using a paired sample t-test, the significance value is .000<.005 and that Finally, eta squared to determine the correlation between the two variables used, the significance value obtained was .395>.005. Thus, the researcher concluded that the dependent variable and independent variable had an influence or influence in improving verbal communication in describing the room and also the application of the PjBL method.